Novel benzylidenehydrazide-1,2,3-triazole conjugates as antitubercular agents: synthesis and molecular docking - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar; Nawale, Laxman; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash; Shingate, Bapurao B. (Mini Reviews in Medicinal Chemistry, 2018)
Novel 1,2,3-triazole based benzylidenehydrazide derivatives were synthesized and evaluated for antitubercular activity against Mycobacterium tuberculosis (MTB) H37Ra, M. bovis BCG and cytotoxic activity. Most of the derivatives exhibited promising in vitro potency against MTB characterized by lower MIC values. Among all the synthesized derivatives, compound 6a and 6j were the most active against active and dormant MTB H37Ra, respectively. Compound 6d was significantly active against dormant and active M. bovis BCG. The structure activity relationship has been explored on the basis of anti-tubercular activity data. The active compounds were also tested against THP-1, A549 and Panc-1 cell lines and showed no significant cytotoxicity. Further, the synthesized compounds were found to have potential antioxidant with IC50 range = 11.19-56.64 μg/mL. The molecular docking study of synthesized compounds was performed against DprE1 enzyme of MTB to understand the binding interactions. Moreover, synthesized compounds were also analysed for ADME properties and from all the experimental results, the potency of compounds indicate that, this series considered as starting point for the developement of novel and more potent anti-tubercular agents in future.